2017
DOI: 10.3390/ma10080916
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Carrier Transport and Crystallographic Orientation Distribution of Transparent Conductive Al-Doped ZnO Polycrystalline Films Deposited by Radio-Frequency, Direct-Current, and Radio-Frequency-Superimposed Direct-Current Magnetron Sputtering

Abstract: We investigated the characteristics of carrier transport and crystallographic orientation distribution in 500-nm-thick Al-doped ZnO (AZO) polycrystalline films to achieve high-Hall-mobility AZO films. The AZO films were deposited on glass substrates at 200 °C by direct-current, radio-frequency, or radio-frequency-superimposed direct-current magnetron sputtering at various power ratios. We used sintered AZO targets with an Al2O3 content of 2.0 wt. %. The analysis of the data obtained by X-ray diffraction, Hall-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
(116 reference statements)
2
20
0
Order By: Relevance
“…As the film thickness increases, μ opt /μ BND gradually decreases while alignment of the columns along (0001) orientation (TC 0002 ) initially increases up to a thickness of 550 nm (Figure 4c). This is similar to the demonstration of Nomoto et al [6] When the carrier concentration is in the range of 5 Â 10 20 cm À3 , the contribution of GB scattering (parabolic nature of the potential barrier created by the depletion region by the carrier trapped at the GB) becomes negligible. Nomoto et al [6] have shown that μ opt /μ GB has a tendency to decrease as the V (0001) increases and proposed a clear correlation between V (0001) and μ Hall /μ GB of AZO films.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As the film thickness increases, μ opt /μ BND gradually decreases while alignment of the columns along (0001) orientation (TC 0002 ) initially increases up to a thickness of 550 nm (Figure 4c). This is similar to the demonstration of Nomoto et al [6] When the carrier concentration is in the range of 5 Â 10 20 cm À3 , the contribution of GB scattering (parabolic nature of the potential barrier created by the depletion region by the carrier trapped at the GB) becomes negligible. Nomoto et al [6] have shown that μ opt /μ GB has a tendency to decrease as the V (0001) increases and proposed a clear correlation between V (0001) and μ Hall /μ GB of AZO films.…”
Section: Resultssupporting
confidence: 89%
“…Nomoto et al have shown that μ opt / μ GB has a tendency to decrease as the V (0001) increases and proposed a clear correlation between V (0001) and μ Hall / μ GB of AZO films. However, in contrast to Nomoto et al, beyond 550 nm, though a mixed orientation appears (orientation of the columns decreases along (0001) and increases along (101false¯1)), μ opt / μ BND keeps on decreasing. Keeping in mind that different growth technique produces films with a large difference in the properties.…”
Section: Resultsmentioning
confidence: 99%
“…These correlations could be associated with the polycrystalline nature of the films and the contribution of grain boundaries in the charge carrier transport in terms of degrading the mobility of electrons, and therefore, the conductivity of the films. Generally, the charge carrier transport in doped semiconductors is limited through three independent scattering mechanisms [80,81]: (1) the scattering by the host-lattice vibration, (2) the ionized scattering due to the distortion resulting from the presence of intrinsic and extrinsic carriers, and (3) the scattering caused by surface defects. Higher values of mobility are expected for the undoped ZnO samples, since the ionized scattering is less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to forming (1) charged boundary surfaces, and also (2) the so-called charge “depletion region” in the bulk of the grains near the boundaries and along them. The charged boundaries establish a potential barrier that impedes the charge transport across the grain boundaries and also inside the bulk along the depletion regions [80,81]. Consequently, the non-affected volume for high-mobility charge transport is expected to be larger for a microstructure with larger grains and a narrower depletion region [83].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies on other possible factors, such as Ar incorporated in the grains and residual stress including both compressive and tensile stress, are required to further build on the results of this study and our previous studies. 20,30,3234,39,73…”
Section: Resultsmentioning
confidence: 99%